Clinical Pathology and Therapeutic Results of Neurilemmoma in the Upper Extremity - K Takase; K Yamamoto; A Imakiire (Journal of Orthopaedic Surgery, 2004)
Purpose. To evaluate the clinical pathology and postoperative outcomes of patients with neurilemmoma in the upper extremity who underwent tumour enucleation, and the correlation factors for neurological deficits apart from enucleation of nerve fascicles. Methods. Magnetic resonance imaging was used to evaluate the state of lesions of the patients with upper-extremity neurilemmoma who underwent tumour enucleation. To find out the correlation factors for neurological deficits, the patients were then divided into 2 groups based on their recovery period—group A (shorter than 6 months) and group B (at 6 months or longer). Duration of the illness, the affected nerve, and the size and histological type of the tumour were then compared between the 2 groups. Results. Of the 20 patients who underwent tumour enucleation for neurilemmoma in the upper extremity, 19 had a single nerve affected and one had multiple lesions involving two nerves. The tumours in 6 patients were of Antoni A type histology and in the remaining 14 patients were of a mixed type. Antoni B type alone was not observed. 15 patients showed postoperative neurological deficits. No neurological deficits were observed in 5 patients. Neurological deficits were fully recovered in all patients except the one with a lesion in the digital nerve. Apart from enucleation of nerve fascicles, the period required for the recovery of neurological deficits was correlated to the duration of the illness (p=0.04) and the histological type of the tumour (p=0.03). Conclusion. Most of the patients with neurilemmoma (95%) had a single nerve affected. A majority of patients (70%) had the mixed type of Antoni A and Antoni B histology; Antoni B type alone was not observed. Neurological deficits were observed in 75% of patients. In patients with neurilemmoma developing in the upper extremity, the period required for recovery from postoperative neurological deficits was short when the duration of illness was short and when Antoni A type histology was present.